LEGAL STUDY ON THE CRIMINAL ACT OF ROBBERY PLANNING AT CIMB COMMERCE BANK BY A GROUP CRIMINAL CRIME AROUND THE REGION MEDAN CITY (CASE STUDY OF DECISION NUMBER 706/PID.B/2011/PN.MDN) - Hasrul Wardana; Muhammad Ridwan Lubis (SEAN Institute, 2022)
Acts of terrorism for any reason are not justified, either in a positive legal framework or in a religious perspective. The acts of terror carried out in Indonesia after the Bali bombings in 2002 have claimed many lives, property, have taken away the right to life and disturbed the peace of the community. For the city of Medan, in addition to the bombing, terror acts were carried out in the form of bank robberies with the motive of radicalism. One of the interesting things to study is tracing the motives of radicalism in the terrorist acts of robbery at the CIMB Niaga Bank in Medan City. the concept of deradicalization to counter terror acts in the future. The focus of this research is the robbery case of Bank CIMB Niaga Medan with the object of research on court decisions against the defendants of the robbery of Bank CIMB Medan. This type of research includes empirical normative research with a case study approach and exploratory analysis. Data collection techniques were carried out through interviews, literature review and focused discussions. The data analysis technique was carried out qualitatively. Qualitative analysis in this study was conducted to find a description of the roots of radicalism in acts of terrorism in the robbery case of Bank CIMB Niaga Medan which had legal force (incracht). This research is planned to be conducted in 1 year with a case study approach and exploratory analysis. Data collection was carried out by studying literature by collecting the results of previous studies and court decisions against convicts of the robbery of Bank CIMB Niaga Medan, then data collection activities were also carried out by means of interviews with criminal law experts and terrorism experts. Based on a literature search and analysis of the Medan District Court's decision Number 706/Pid.B/2011/PN.Mdn dated August 2, 2011 which tried the perpetrators of the Medan City Branch of the CIMB Niaga Bank Robbery, information was obtained that there was no connection with the crime of terrorism. The Medan District Court has decided on 14 defendants, all of whom were legally and convincingly proven to have committed acts of terrorism. The defendant's mistakes under the provisions of the Terrorism Law are different from each other and the criminal events that have been proven to be proven also vary, because the defendants are not all perpetrators of the robbery of Bank CIMB Niaga Medan. Based on the judge's verdict from the Medan District Court's decision, it was concluded that there was no radical motive in the terrorism case of the Medan City Bank CIMB Niaga robbery.